Hubungan Kemampuan Berpikir Kreatif Dan Menulis Deskripsi Pada Siswa Kelas II Sekolah Dasar - Budi Febriyanto Febriyanto; Rahman; Yuliawati; Sri Wulan Anggraeni; Devi Afriyuni Yonanda (Elementary Teacher Education Program, Majalengka University, 2023)
Writing activities are creative activities, through learning to write students can develop their creative potential. There are many benefits that can be gained from writing, including increasing intelligence, developing initiative and creativity, growing courage, encouraging the will and ability to gather information. However, the reality in the field shows that students in writing narrative essays have not been able to express their correct ideas as clearly as possible. This shows that students' creative thinking skills in writing narrative essays are still low and causes only a few students to be capable of creative thinking skills in writing narrative essays, especially in the lower classes. The aim to be achieved in this research is to determine the relationship between creative thinking and elementary school students' descriptive writing abilities. This research is correlational research (Correlational Studies) to determine the relationship between the ability to think creatively and the ability to write descriptions. The results of the research concluded that there is a relationship between creative thinking and elementary school students' descriptive writing abilities.